2022
DOI: 10.1016/j.clinbiomech.2021.105538
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the feasibility and effectiveness of treadmill-based perturbations for assessing and improving walking stability in chronic obstructive pulmonary disease

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…However, increasing intensity, frequency and duration of such protocols could also have disadvantages such as activity-induced fatigue and reduced participation, particularly in certain clinical populations with significant health issues and balance impairments (Romberg et al, 2004. Another alternative for those unable to tolerate a high dose within a single session is to provide more sessions with fewer training trials or minutes per session (McCrum et al, 2022). For example, studies have shown that a single slip exposure administered in separate, frequent sessions can induce lasting effects within the same environment (i.e., laboratory) Pai, 2009b, Liu et al, 2017).…”
Section: What Is the Dose-response Relationship For Pbt?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing intensity, frequency and duration of such protocols could also have disadvantages such as activity-induced fatigue and reduced participation, particularly in certain clinical populations with significant health issues and balance impairments (Romberg et al, 2004. Another alternative for those unable to tolerate a high dose within a single session is to provide more sessions with fewer training trials or minutes per session (McCrum et al, 2022). For example, studies have shown that a single slip exposure administered in separate, frequent sessions can induce lasting effects within the same environment (i.e., laboratory) Pai, 2009b, Liu et al, 2017).…”
Section: What Is the Dose-response Relationship For Pbt?mentioning
confidence: 99%
“…However, there is also emerging evidence for the effectiveness of PBT in 'high risk' older adults (for example assisted living residents, or older adults with a history of falls or balance problems), and people with Parkinson's disease, stroke and multiple sclerosis (Shimada et al, 2004, Protas et al, 2005, Smania et al, 2010, Shen and Mak, 2015, Aviles et al, 2019, Bhatt et al, 2019, Handelzalts et al, 2019, Dusane and Bhatt, 2020, Mohamed Suhaimy et al, 2020, Dusane and Bhatt, 2021. PBT trials have also been conducted in people with chronic obstructive pulmonary disorder (McCrum et al, 2022) and incomplete spinal cord injury (Unger et al, 2021)), but due to limited findings will not be discussed in detail in this article. Previous reviews (Mansfield et al, 2015, Gerards et al, 2017 showed significant fall reductions in community-dwelling older adults, frail/high-risk older adults and people with Parkinson's disease and stroke following PBT.…”
Section: What Is the Evidence For Pbt In Clinical Populations?mentioning
confidence: 99%
“…Following a break, the same fixed-speed walking trials were repeated and recorded. During another break, the data from these trials were used to calculate a stability-normalised walking speed for each participant individually for use in the subsequent walking perturbation trial, which was set for a margin of stability (MoS; see below; [68]) of 0.05m as described previously [69], ensuring a comparable baseline walking stability for all groups [70][71][72][73]. Next, participants completed the perturbation trial which started with three to four minutes of unperturbed walking at the stability-normalised walking speed, followed by 10 unannounced unilateral treadmill belt acceleration perturbations (every 30 to 90 seconds).…”
Section: Stability During Perturbed Walkingmentioning
confidence: 99%
“…Foot touchdown and toe-off were detected using a combined method of force plate data (50 N threshold) and foot marker data [74], as described in detail previously [75]. The anteroposterior MoS at foot touchdown were calculated as the anteroposterior distance between the anterior boundary of the base of support (BoS) and the extrapolated centre of mass (XCoM) [68], adapted for our validated reduced kinematic model [76] and treadmill walking [77], in the same manner as our previous studies [69][70][71][72]. The MoS was calculated for the following steps: the mean MoS of the eleventh to second last step before each perturbation (Base); the final step before each perturbation (Pre); and the first eight recovery steps following each perturbation (Post1-8).…”
Section: Stability During Perturbed Walkingmentioning
confidence: 99%
See 1 more Smart Citation